위험음주를 하는 직장인의 중독 성향 및 성격 - 전민, 이주연, 홍지은, 유태영, 김선영, 김재민, 신일선, 윤진상, 김성완 (Singyŏng chŏngsin ŭihak, 2017)
Objectives This study examined psychiatric characteristics including addictive behavior and personality traits among workers with hazardous drinking. Methods The cross-sectional study included 486 workers. Socio-demographic and clinical variables were collected, and employed the Alcohol Use Disorders Identification Test-Korean version (AUDIT-K), Korean translation of the Internet Addiction Test, Smartphone Addiction Scale, Hospital Anxiety and Depression Scale (HADS), Perceived Stress Scale (PSS), Korean version of Connor-Davidson Resilience Scale (K-CD-RISC), Big Five Inventory-Korean version-10 (BFI-K-10). Hazardous drinking was identified with the AUDIT-K score of 10 in men and 6 in women. Univariate and logistic regression analysis were used to identify factors associated with hazardous drinking. Results One hundred sixty-eight (34.6%) workers reported hazardous drinking. It was more common in men and workers with lower levels of education, workers that smoked and experienced smartphone addiction, and had experienced attempted suicide. Among the assessment scales, scores on the HADS and PSS were higher, and scores on the K-CD-RISC were lower for these workers. Regarding scores for the BFI-K-10, higher extraversion, lower agreeableness, and lower openness were related to hazardous drinking. Logistic regression analysis revealed that smoking, smartphone addiction, history of attemptd suicide, and higher scores on extraversion of the BFI-K-10 were significantly associated with hazardous drinking. Conclusion Our findings demonstrate that hazardous drinking tends to coexist with other addictive behaviors such as smoking and smartphone addiction. Clinicians should also be aware of suicidal risk in people with hazardous drinking. KCI Citation Count: 1